CHANGES IN THE COSTS OF HYPERTENSIVE CRISIS THERAPY DUE TO OPTIMIZATION OF DRUG SUPPLY IN THE PRE-ADMISSION CARE - N. I. Gaponova; N. F. Plavunov; V. L. Baratashvili (Рациональная фармакотерапия в кардиологии)
Aim. To assess the changes in the costs of treatment of patients with hypertensive crisis (HC) in pre-admission care in Moscow from 2005 to 2010. Material and methods. Comparative analysis of the treatment costs was performed depending on outcomes in patients with HC at Moscow Emergency Medical Care Station named after A.S. Puchkov. HC arresting excluding the need of admission was taken into account in addition to antihypertensive effect and safety in evaluation of pre-admission care efficacy. Results. Introduction in practice of modern algorithms of emergency pre-admission care, supply of ambulance crews with modern antihypertensive drugs reduced the rate of admission from 71% in 2005 to 44% in 2010 among patients with HC. Total savings amounted to 403,691,808 rubles. Conclusion. Introduction of modern technologies in the emergency pre-admission care for patients with HC is economically reasonable.